The medical dictionary user as an active participant in its development - Gordiyenko, Olena V.; Гордиенко, Елена Вячеславовна; Гордієнко, Олена В'ячеславівна (Poland, Warsaw, 2020)
The article is written within the framework of such a direction of linguistics as terminological lexicography. The mechanism for conducting a questionnaire among students and teachers, in order to study the user's needs in creating a medical dictionary, has been developed. The user is considered as a direct participant in the development of an English medical dictionary. The methodology of the work is complex and includes the following methods: analytical review of the literature, the method of lexicographic analysis, the method of critical analysis, the method of comparative and comparative-analytical analysis. The questionnaire is compiled taking into account such lexicographic parameters as information presentation, time perspective, vocabulary inclusion, number of languages, purpose, addressee, size and form of the dictionary. The prospect of the study is to carry out the questionnaire proposed in the article and develop the design of a medical dictionary. Статья выполнена в рамках такого направления лингвистики как терминологическая лексикография. В статье разработан механизм проведения анкетирования среди студентов и преподавателей, с целью изучения потребностей пользователя при создании медицинского словаря. Пользователь рассматривается как непосредственный участник разработки англоязычного медицинского словаря. Методология работы носит комплексный характер и включает в себя следующие методы: аналитический обзор литературы, метод лексикографического анализа, метод критического анализа, метод сопоставительного и сопоставительно-аналитического анализа. Анкета составлена с учётом таких лексикографических параметров как подача информации, временная перспектива, включение лексики, количество языков, цель, адресат, размер и форма словаря. Перспективой исследования является проведение, предложенного в статье анкетирования, и разработка дизайна медицинского словаря.
Пользователь медицинского словаря как активный участник его разработки
Keywords: lexicography; medical term; medical dictionary; user needs; questionnaires; lexicographic parameters; лексикография; медицинский термин; медицинский словарь; потребности пользователя; анкетирование; лексикографические параметры